Ketogenic Diet Improves Gut Microbiome and Alzheimer's Disease Markers (FS09-02-19). (24th October 2019) - Nagpal, Ravinder; Wang, Shaohua; Neth, Bryan; Kawas, Mohammad; Craft, Suzanne; Yadav, Hariom
Abstract: Objectives: To compare the gut microbiome and short-chain fatty acids (SCFAs) in subjects with or without mild cognitive impairment (MCI) and study the effect of a modified Mediterranean-ketogenic diet (MMKD) and a low-fat American Heart Association Diet (AHAD) on gut microbiome, SCFAs, and cerebrospinal fluid (CSF) biomarkers of AD. Methods: A randomized crossover study of MMKD and AHAD interventions is performed on 17 subjects (mean age 63.4 yr) with ( n = 11) or without ( n = 6) MCI. Subjects undergo MMKD and AHAD intervention for 6-weeks separated by 6-weeks washout. Gut microbiome at the beginning and end of each intervention is analyzed by 16S rRNA gene sequencing and QIIME analysis. Fecal SCFAs are measured by HPLC, and AD biomarkers like amyloid β-40 (Aβ40) and Aβ42, total tau and phosphorylated tau-181 (ptau) are measured in CSF. Results: At baseline, subjects with or without MCI show no notable difference in microbiome diversity but show specific microbial signatures associated with MCI status. MCI +ve subjects have higher abundance of Firmicutes, Proteobacteria, Enterobacteriaceae, Coriobacteriaceae, Mogibacteriaceae, Phascolarctobacterium and Coprococcus that correlates with lower Aβ40 and Aβ42 and higher tau and ptau. Proteobacteria correlate positively with Aβ42:Aβ40 while propionate correlates negatively with Aβ42 in MCI +ve subjects. The abundance of Enterobacteriaceae, Akkermansia, Slackia, Christensenellaceae and Erysipelotriaceae is increased while that of Bifidobacterium and Lachnobacterium is reduced by MMKD; whereas AHAD increases Mollicutes _Rf39. MMKD slightly reduces lactate and acetate while increasing propionate and butyrate. Conversely, AHAD increases acetate and propionate while reducing butyrate. Conclusions: Specific gut microbial signatures can present as markers of MCI. MMKD can modulate the gut microbiome and metabolites in association with improved AD biomarkers, suggesting that MMKD could ameliorate MCI or AD in humans. Funding Sources: National Institutes of Health; US Department of Defense; Center for Diabetes, Obesity and Metabolism at the Wake Forest School of Medicine.